Corporate Governance Mechanisms and Firm Performance in Iraq: A Conceptual Framework - Talab, Hassnain Raghib; Abdul Manaf, Kamarul Bahrain; Abdul Malak, Siti Seri Delima (Everant Publishers Pvt Ltd, 2017)
There is a need for consistency in the aim of the Iraqi government to attract more foreign investors into Iraq for the purpose of stimulating economic growth and development through sound corporate governance practice.This study is grounded on the review of past literatures based on which the proposed conceptual framework was developed and discussed.The relationship between corporate governance mechanisms and firm performance is validated and established via extant scholarly researches.This conceptual study therefore proposed a corporate governance model for the enhancement of the Iraqi listed companies’ performance.The model is aimed to resolve the lingering problem of poor firm performance via the various identified internal and external corporate governance mechanisms which reflect the economic and reporting climate of Iraq.This model can be subjected to empirical validation via the collection and analysis of relevant data.The proposed conceptual framework creates a case for both policy makers and management of listed companies in Iraq on the significance of sound corporate governance.The proposed conceptual framework is unique and comprehensive compared to the few studies on corporate governance that emanated from Iraq. In this paper, internal audit function establishment and the training of internal audit department staff are proposed to serve as internal monitoring mechanisms.Through the two mechanisms, Iraqi listed company’s performance can be enhanced.